Upaya Meningkatkan Motivasi Belajar Siswa Melalui Model Pembelajaran Game Based Learning (GBL) Pada Mata Pelajaran PKN Di Kelas IV SDN 2 Botupingge - Nurfatimah Kaili; Abd. Hamid Isa; Fandi H. Binggo (Transbahasa, 2026)
This study aims to improve students’ learning motivation through the implementation of the Game Based Learning (GBL) model in Civic Education (PKn) for fourth-grade students at SDN 2 Botupingge. This research employed Classroom Action Research (CAR) based on the model of Stephen Kemmis and Robin McTaggart, conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 12 students. Data were collected through observation, interviews, and documentation. Data analysis was carried out using qualitative and quantitative approaches by calculating the percentage of students’ learning motivation achievement. The results showed that the implementation of the Game Based Learning model significantly improved students’ learning motivation. The initial motivation level was 8%, which increased to 42% in the first cycle and reached 92% in the second cycle. This indicates that most students achieved a high level of learning motivation. The implementation of Game Based Learning proved to be effective in creating an engaging, interactive, and student-centered learning environment. Therefore, this model can be used as an alternative instructional strategy to enhance students’ learning motivation in Civic Education at the elementary school level.